Pequeños grandes préstamos (2017)
Pequeños Grandes Prústamos is a service that gives power to the neighborhood shops. The project seeks to generate credit option in mom and pop shops, through a prepaid credit card, where the community can access to the fianza (credit) and the grocers keep track of their loans. Therefore, the service seeks to encourage support for small businesses through an alliance with Aflore where the entrepreneur with the best management of his card will be sponsored by his shopkeeper and will get a credit in order to improve his business idea. The project positions the shopkeepers o tenderos as an actor of change, which allows the community to approach the banking sector and access to short-term loans, through tools that support this friendly informality under which many shopkeepers work in our country. It is based on an inclusive model that allows the immersion of a new segment to savings and credit possibilities. Pequeños Grandes Prústamos is aware of the importance of shopkeepers in society, which is why it makes them a manager of resources, opportunities and dreams within their neighborhoods.